2020
DOI: 10.1007/s13197-020-04365-x
|View full text |Cite
|
Sign up to set email alerts
|

Effect of extreme heat processing on the Moroccan Zantaz’ honey antioxidant activities

Abstract: The effect of an extreme heat processing on Zantaz honey samples was studied using a panel of physicochemical parameters, antioxidant activities and FTIR-ATR spectroscopy. Honey samples were heated at 121°C for 30 min and the heat processing effect was confirmed indirectly through the assessment of hydroxymethylfurfural content, for which the values increased significantly (p \ 0.01), and diastase activity, which was totally absent after the thermal processing. Besides, the effects of the heat on the antioxida… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
18
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 17 publications
(20 citation statements)
references
References 37 publications
2
18
0
Order By: Relevance
“…In contrast, at high initial concentration, the radical scavenging activity decreased. Elamine et al (2020) observed increased content of melanoidins at similar processing conditions (120 • C, 30 min). However, such extreme processing conditions darkened the honey.…”
Section: -Picrylhydrazyl [Free Radical Scavenging Activity] [Dpph] Ferric Reducing Antioxidant Power [Antioxidant Capacity] [Frap] 22′-azsupporting
confidence: 52%
See 1 more Smart Citation
“…In contrast, at high initial concentration, the radical scavenging activity decreased. Elamine et al (2020) observed increased content of melanoidins at similar processing conditions (120 • C, 30 min). However, such extreme processing conditions darkened the honey.…”
Section: -Picrylhydrazyl [Free Radical Scavenging Activity] [Dpph] Ferric Reducing Antioxidant Power [Antioxidant Capacity] [Frap] 22′-azsupporting
confidence: 52%
“…In contrast, it increased the antioxidant activity in honey with lower initial pigment content (thyme and orange honey) (Karabagias et al, 2018). According to Elamine et al (2020), heating lightcolored honey, honey with lower amounts of polyphenols, or lower antioxidant activity induces more accentuated changes than those observed in darker honey or those already possessing higher amounts of polyphenols or higher antioxidant activity. For instance, Kowalski (2013) demonstrated that TPC and antioxidant activity in lightcolored lime honey increased after thermal processing (90 • C for 60 min), whereas in dark, phenolic compoundsrich honeydew honey the opposite effect was observed.…”
Section: -Picrylhydrazyl [Free Radical Scavenging Activity] [Dpph] Ferric Reducing Antioxidant Power [Antioxidant Capacity] [Frap] 22′-azmentioning
confidence: 99%
“…Other authors [34], also demonstrated that phenolic compounds possess potent effects on antioxidant effects due to the ability for scavenging superoxide anion radicals. At the same time, [35] affirms that the polyphenolic contents in honey are linked to high superoxide scavenging activity. The Zantaz honey (Bupleurum spinosum pollen as predominant species) from Morocco [35], had recorded an IC 50 values of 50.91 mg/mL for the superoxide activity, a very low activity compared to that found in our E. officinarum honey M7:IC 50 = 1.95 mg/mL.…”
Section: Enzymatic Activitiesmentioning
confidence: 68%
“…The presence of RSC in honey is crucial for predicting crystallization ( Escuredo et al . 2014 ), as exceeding the saturation level leads to the formation of crystals in honey ( Bhandari & Bareyre 2003 ), which affects its shelf life ( Elamine et al . 2020 ).…”
Section: Discussionmentioning
confidence: 99%